The alloy tree : a guide to low-alloy steels, stainless steels and nickel-base alloys - Farrar, J. C. M. (CRC Press ; Woodhead Pub., 2004)
The alloy tree is a user-friendly, logical guide to the major metal alloys and their variants. Introductory chapters present a diagrammatic representation of a main alloy route map, which categorises each specific type of alloy. New types of metals that are all members of the same family can be developed, by adding different alloys together. Chemical formulas are given for each individual metal alloy. Data tables with information on designation (definition), description, background, chemical composition, properties, microstructure and applications are given for each alloy group. This book is a.